2022
DOI: 10.3389/fonc.2022.840871
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Shortest Path Length of the Sensorimotor Network Induces Frontal Glioma-Related Epilepsy

Abstract: BackgroundGlioma-related epilepsy (GRE) is a common symptom in patients with prefrontal glioma. Epilepsy onset is associated with functional network alterations. This study investigated alterations of functional networks in patients with prefrontal glioma and GRE.MethodsSixty-five patients with prefrontal lobe gliomas were retrospectively assessed and classified into GRE and non-GRE groups. Additionally, 25 healthy participants were enrolled after matching for general information. Imaging data were acquired wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, some studies suggest that tumor invasion affects brain function over the whole network rather than isolated regions ( Vigneau et al, 2006 ; Xiang et al, 2010 ; Briganti et al, 2012 ). In particular, some studies indicated that tumor-related epilepsy induces topological changes in WM networks ( Zhou et al, 2022 ) and functional networks ( Fang et al, 2022 ). Therefore, the network-based features and the structural features outside the tumor lesion can reflect more information about glioma-related epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some studies suggest that tumor invasion affects brain function over the whole network rather than isolated regions ( Vigneau et al, 2006 ; Xiang et al, 2010 ; Briganti et al, 2012 ). In particular, some studies indicated that tumor-related epilepsy induces topological changes in WM networks ( Zhou et al, 2022 ) and functional networks ( Fang et al, 2022 ). Therefore, the network-based features and the structural features outside the tumor lesion can reflect more information about glioma-related epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor invasion of the frontal lobe induces changes in the executive control network (ECN) ( Liu Y. et al, 2020 ). Similarly, the onset of epilepsy also leads to functional network alterations ( Cao et al, 2014 ; Fang et al, 2022 ). Therefore, an in-depth understanding of the structural and functional patterns of the ECN in glioma-associated epilepsy is required for the early differentiation and diagnosis of glioma seizures and the development of individualized intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the changes in cerebral network caused by glioma and GRE are not completely clear. Around frontal and temporal GRE and in regard to graph theory analysis based on rs-fMRI, Fang et al found that both frontal lobe and temporal lobe GRE will cause changes in the topological properties of brain functions, and temporal lobe GRE can cause changes in the topological properties of visual networks (80) and language networks (81); prefrontal lobe GRE can cause changes in the topological properties of sensorimotor networks (82). Meanwhile, Zhou et al (83) identified altered topological properties of epilepsy-related white matter network in patients with frontal glioma.…”
Section: Robustnessmentioning
confidence: 99%
“…Previous studies 9–12 have demonstrated that different tumor locations cause alterations in different functional networks near the tumor. For instance, increased functional connectivity (FC) of nodes located in the premotor area and decreased shortest path length of the sensorimotor network are specific alterations in patients with prefrontal glioma and GRE onset 13 …”
Section: Introductionmentioning
confidence: 99%